2009
DOI: 10.1002/ajpa.20999
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of the os pubis: Implications for the Suchey‐Brooks method

Abstract: Studies of skeletal development frequently document populational incidences of bilateral asymmetry. Degenerative morphological skeletal changes, attributed to age related and irregular ossification, may also progress asymmetrically, either as the result of asymmetric biomechanical factors expressed over the lifespan, asymmetric expression of physiological processes, or progressive magnification of asymmetry acquired previously during development. This study illustrates the effects of bilateral asymmetry on age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 15 publications
0
22
2
1
Order By: Relevance
“…The results of the current study disagree with previous findings that have shown high prevalence of asymmetry for the Suchey–Brooks system as noted in over 60% of the samples analyzed . Specifically, this study does not detect either (i) the greater magnitude of asymmetry with increased age or (ii) the directional asymmetry favoring the right side .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of the current study disagree with previous findings that have shown high prevalence of asymmetry for the Suchey–Brooks system as noted in over 60% of the samples analyzed . Specifically, this study does not detect either (i) the greater magnitude of asymmetry with increased age or (ii) the directional asymmetry favoring the right side .…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to Overbury et al., 2009 , the number of more accurate “older” estimates was compared to the number of more accurate “younger” estimates to test whether the “older” or “younger” side offered consistently better age approximation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… study) found a moderate amount of asymmetry. This indicates that bilateral asymmetry in phase allocation, while not a trait observed in Western Australia, is a common feature observed in Eastern Australian individuals and in other populations of Thailand and North America . Thus, there is a continued recommendation to score pubic symphyses in isolation.…”
Section: Discussionmentioning
confidence: 92%
“…Both left and right pubes should be incorporated into further investigations, both as a source of confirmation of estimated skeletal age in light of possible asymmetry (cf. [57]) and as a check against pathological conditions that affect pelvic trabeculae and may do so asymmetrically (e.g., Paget's disease of bone). The lack of anisotropy measures in the plain film radiographic modality, where increased medio-lateral orientation of trabeculae is qualitatively apparent, should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%